Rotavirus genotypes in children with gastroenteritis in Erzurum: first detection of G12P[6] and G12P[8] genotypes in Turkey - Hakan Aydin; Osman Aktaş (Gastroenterology Review)
Introduction : Rotavirus is one of the leading pathogens which cause acute gastroenteritis in children and is responsible for a substantial proportion of childhood deaths worldwide. Aim: To determine the group A rotavirus (RVA) prevalence and genotypes of circulating RVA strains in 0–5-year-old children with complaints of vomiting and diarrhoea in Eastern Anatolia in Turkey. Material and methods : RNA extracted from stool specimens of 329 children aged 0–5 years with acute diarrhoea was subjected to reverse transcription polymerase reaction (RT-PCR) and multiplex-nested PCR. The genotypes were identified based on the expected size of the amplicon, which was amplified with a genotype-specific primer. Results: Out of 329 stool samples analyzed, 109 (33.1%) were positive for RVA. G1P[8] was the dominant genotype combination (42.2%), followed by G9P[8] (21.1%) and G12P[6] (11.0%). Mixed infections were identified in 5 cases: G3,9 in 2 cases, G1,9 in 1 case, P[4,8] in 1 case, and P[6,8] in 1 case. The P genotype could not be typed in two patients. Conclusions : In the study, we detected six different rotavirus G genotypes, 3 different P genotypes, 11 different G-P combinations and 5 different mixed genotypes combinations. G1, G9, G12 and P[8] were found to be the predominant genotypes. G12P[6] and G12P[8] genotypes, showing an increase as new rotavirus genotypes in the world, are reported for the first time for our regions. We determined the dominant genotypes, mixed genotypes and unconventional genotypes of rotavirus in our region.